"A distribuição espacial das arboviroses e dos seus determinantes socioambientais : o caso de Boa Vista, Roraima (2010-2019)" - Castro, Alexsandra Araujo de (Universidade Federal de Roraima, 2022)
In recent decades, the Geography of Health has taken on an even more prominent place, not only regarding the study of spatial variations of diseases, but also on the health-disease process determined by socio-environmental conditions, which has expanded the explanations and helped in the understanding of arboviruses, diseases already assumed to be a major Public Health problem and great social and economic impacts. So much so that contemporary Brazil is the country with the highest number of reported cases of arboviruses, and Boa Vista, capital of Roraima, after years of eradicating dengue, in 1981, was responsible for the return of the disease to the country, which since then, began to suffer recurrent epidemics not only of dengue, but also of Zika and chikungunya. This study, therefore, aims to analyze the spatial distribution of arboviruses (dengue, zika, chikungunya and yellow fever) and their socio-environmental determinants in the urban area of Boa Vista, Roraima between 2010 and 2019, based on the identification, characterization and cartographic representation of the census sectors with the highest occurrences. Therefore, the methodology used an exploratory and descriptive analysis, supported by a bibliographical and documental research based on the Geosystemic Method and on statistical and geoprocessing techniques. The results showed that the local and environmental characteristics of Boa Vista, such as rainfall, slope, river network, lack or precariousness of sanitation services, income and education, favored the increased proliferation of the vector mosquito and, thus, of the cases of arboviruses, a situation observed, with greater intensity, in the neighborhoods in the west zone. Boa Vista was responsible for 66% (R$ 582,901.40) of the total expenses of hospital admissions in the State of Roraima; it was also the 3rd capital of the North Region with the highest expenses in hospitalizations for arboviruses. Finally, it was highlighted that for the control of vectors and arboviral epidemics, in Boa Vista, isolated combat actions are not enough, joint attitudes are needed against the multifactorial aspects that determine such diseases.